Gambaran stres akademik pada mahasiswa pendidikan kepelatihan olahraga semester vi - Iskandar, Iskandar (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Baground: Academic stress is a state in which a student feels incapable dealing with the pressures and demands faced in the academic world and considering These demands are seen as a disturbance. Students need to manage academic stress. by dealing with anxiety, thinking positively when facing problems, and so on. the most important thing is to seek social support from parents or family Purpose: To dentified the picture of academic stress in sports coaching education students in semester VI. Methods: A quantitative type with a descriptive design.SThe sample of this research was 96 students of the PKO Study Program, semester VI, IKIP PGRI Kaltim, using the sampling technique.proportional stratified random sampling. Instruments used Perceived Academic Stres Scale (PASS). Results: Based on the characteristics of respondents by age, almost all of them are aged 17-25 years as many as 94 students (97.9%), gender is mostly male as many as 72 students (75.0%), employment status is almost all unemployed as many as 81 students (84.4%), and almost half of them live in boarding houses/rented accommodation/dormitories as many as 45 students (46.9%). Based on academic stress, almost all of them experience moderate academic stress as many as 71 students (74.0%). Conclusion: Almost all PKO semester VI experience moderate academic stress. It is expected that educational institutions can monitor the psychological conditions of students such as preparing counseling guidance and providing knowledge through seminars on stress management for students so that they are able to manage stress well and adaptively. Keywords: Academic Stress; Education; Students. Pendahuluan: Stres akademik keadaan seorang mahasiswa merasa tidak mampu menangani tekanan dan tuntutan yang dihadapi dalam dunia akademis serta menganggap tuntutan tersebut sebagai suatu gangguan. Mahasiswa perlu mengelola stres akademik dengan cara menangani kecemasan, berpikir positif ketika menghadapi masalah, dan yang terpenting mencari dukungan sosial dari orang tua atau keluarga Tujuan: Untuk mengidentifikasi gambaran stres akademik pada mahasiswa pendidikan kepelatihan olahraga semester VI IKIP PGRI Kaltim tahun akademik 2024/2025. Metode: Jenis kuantitatif dengan desain deskriptif. Sampel penelitian ini mahasiswa Prodi PKO semester VI IKIP PGRI Kaltim berjumlah 96 orang, teknik pengambilan sampel menggunakan teknik proportional stratified random sampling. Instrumen menggunakan Perceived Academic Stres Scale (PASS). Hasil: Berdasarkan karakteristik responden berdasarkan usia, hampir seluruhnya berusia 17-25 tahun sebanyak 94 mahasiswa (97.9%), jenis kelamin sebagian besar laki-laki sebanyak 72 mahasiswa (75.0%), status pekerjaan hampir seluruhnya belum bekerja sebanyak 81 mahasiswa (84.4%), dan hampir setengahnya tinggal di kost/kontrakan/asrama sebanyak 45 mahasiswa (46.9%). Berdasarkan stres akademik hampir seluruhnya mengalami stres akademik sedang sebanyak 71 mahasiswa (74.0%). Simpulan: Hampir seluruh mahasiswa PKO semester VI IKIP PGRI Kaltim mengalami stres akademik sedang. Diharapakan intitusi pendidikan dapat memonitor kondisi psikologis mahasiswa seperti menyiapkan bimbingan konseling dan memberikan pengetahuan melalui seminar tentang manajemen stres untuk mahasiswa agar mereka mampu mengelola stres dengan baik dan adaptif. Kata Kunci: Stres Akademik; Mahasiswa; Pendidikan.